Exploring Lithium Deficiency in Layered Oxide Cathode for Li‐Ion Battery. (23rd June 2017) - Cho, Sung‐Jin; Uddin, Md‐Jamal; Alaboina, Pankaj K.; Han, Sang Sub; Nandasiri, Manjula I.; Choi, Yong Seok; Hu, Enyuan; Nam, Kyung‐Wan; Schwarz, Ashleigh M.; Nune, Satish K.; Cho, Jong Soo; Oh, Kyu Hwan; et al.
Abstract : The ever‐growing demand for high capacity cathode materials is on the rise since the futuristic applications are knocking on the door. Conventional approach to developing such cathode relies on the lithium‐excess materials to operate the cathode at high voltage and extract more lithium‐ion. Yet, they fail to satiate the needs because of their unresolved issues upon cycling such as, for lithium manganese‐rich layered oxides—their voltage fading, and for as nickel‐based layered oxides—the structural transition. Here, in contrast, lithium‐deficient ratio is demonstrated as a new approach to attain high capacity at high voltage for layered oxide cathodes. Rapid and cost effective lithiation of a porous hydroxide precursor with lithium deficient ratio is acted as a driving force to partially convert the layered material to spinel phase yielding in a multiphase structure (MPS) cathode material. Upon cycling, MPS reveals structural stability at high voltage and high temperature and results in fast lithium‐ion diffusion by providing a distinctive solid electrolyte interface (SEI) chemistry—MPS displays minimum lithium loss in SEI and forms a thinner SEI. MPS thus offers high energy and high power applications and provides a new perspective compared to the conventional layered cathode materials denying the focus for lithium excess material. Abstract : Lithium deficiency is demonstrated as an original approach to reach high capacity at high voltage for layered oxide cathodes by obtaining an intrinsically stable multiphase structure (MPS) cathode material with coexisting layered and spinel phase. The presence of spinel phase in MPS cathode stabilizes the structure and results in high performance at both room and high temperature.